2021
DOI: 10.3897/popecon.5.e77832
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of COVID-19 vaccine uptake in Russia in the context of mandatory vaccination of employees

Abstract: The paper offers an analysis of socio-demographic factors determining uptake of COVID-19 vaccine in Russia in 2021. The study focuses in particular on the role of mandatory vaccination of workers in certain sectors of the economy. The study is empirically based on three rounds of a nationally representative telephone survey, conducted in February–October 2021, which investigated the situation and behaviour of a cross section of the Russian adult population in the context of the spread of coronavirus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…In addition, people with high education had higher odds (AOR=2, 95% CI (0.95;5.53]) to adhere to COVID-19 measures than those with no education. These results are in opposite to what were found in Maleva et al, (2021) who pointed out the key factors behind vaccine uptake are age and education of the individual. People in older age groups and people with higher education were likely to incline towards vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, people with high education had higher odds (AOR=2, 95% CI (0.95;5.53]) to adhere to COVID-19 measures than those with no education. These results are in opposite to what were found in Maleva et al, (2021) who pointed out the key factors behind vaccine uptake are age and education of the individual. People in older age groups and people with higher education were likely to incline towards vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…This compares unfavourably to even the global figure of around 60%, and is lower than in Pakistan and The Philippines. Maleva et al [ 42 ] found that Russian young people and people with low levels of education are the least likely to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Explaining the relationship between these factors and vaccine hesitancy is of considerable interest. On the one hand, people with higher education have higher access to diverse sources of information about vaccination and are more likely to trust scientists and doctors (Maleva et al 2021). Furthermore, people with a higher level of education and income tend to show a proactive attitude towards their health, they are more likely to take responsibility for individual decisions on health (Eide, Showalter 2011).…”
Section: Analysis Of Distrust In Vaccination Against Covid-19mentioning
confidence: 99%
“…First, these are factors of availability of vaccination services -place of residence, income and employment status (Sallam 2021). Second, vaccination behavior was also influenced by different forms of coercion on the part of the state and employers: from bans on service delivery to people without vaccination certificates to dismissal of those who refused to be vaccinated (Maleva et al 2021). However, forced vaccination has significant costs, both organizational and economic ones as well as directly related to the vaccination campaign itself -it can cause rejection and contribute to radicalization of the position of those population groups who are negative or hesitant about vaccination.…”
Section: Introductionmentioning
confidence: 99%